Urban food systems profile: Sri Lanka - Ramamoorthi, Dushiya; Drechsel, Pay (International Water Management Institute (IWMI). CGIAR Initiative on Resilient Cities, 2024)
The most populated (urban) area in Sri Lanka is its Western Province with Colombo, Sri Lanka’s commercial capital. This “Megapolis” depends for its food supply significantly on different geographical areas of Sri Lanka. These foodsheds differ by commodity. Peri-urban agriculture plays a minor role and until very recently, urban farming did not get (institutional) attention, although the role of both, urban and peri-urban agriculture is mentioned in the national agricultural policy. The policy also calls for the identification and strengthening of city region food system (CRFS) to better link rural and urban communities, also in view of climate shocks and other disasters. The need for this became clear during the Covid-19 epidemic and subsequent economic crisis of the country when the Colombo Municipal Council started actively to support urban food production.